Educational evaluation from pedagogical praxeology: problems of concept and context - Francisco De Asís Perea Mosquera; Hilda Marlén Rubio González; Roberto Herrera Correa (Corporación Universitaria Minuto de Dios, 2004)
Nowadays the evaluation must be focused as a process which involve different actors participating in it. It should be done following the directriz established by the institution. Based on the theoretical fundaments from praxeology, always looking for the reflex ion and actions leading to the improvement of quality. As a summary, it should take into account the apprenticeship, the curriculum, and the evaluation itself.